The Role And Contribution Of Teacher Professional Allowances To Teacher Welfare In Medan City - M. Alif Al-Hasyir Hrp; Syawaluddin Nasution (Jurnal Ilmu Sosial Mamangan, 2024)
This research aims to determine the benefits of educator certification in the performance and commitment of teachers or educators in providing maximum learning to students in return for the welfare of educators in Medan City. The consequences of this research show that the commitment to sending expert remittances to educators is very important, especially considering the government's strategy in government assistance to educators in Indonesia. To produce educators who have great capacity and gifts in educational experience, government assistance and salaries must be provided. This research uses qualitative methods with data collection techniques, data reduction, and data presentation and drawing conclusions. Data collection is done by observation, interviews and documentation to get the results the researcher needs. From the results of the research, it was found that professional allowances or educator certification allowances help increase the wages or rewards of teachers or instructors in their daily lives because certified educators are no longer in doubt in carrying out teaching and learning activities due to obtaining educators certification first. First, go through the requirements that must be met as an educator.